Analisis Struktur Lapisan Tanah Menggunakan Metode Geolistrik Resistivitas Konfigurasi Schlumberger Vertikal di Kompleks Perumahan Dosen Uncen Kali Acai, Kulurahan VIM, Distrik Abepura, Kota Jayapura - Mantiri, Steven Yohanes Yulianus; Alwendzani, Vinexa; Napitupulu, Daniel; Sutarman, Tatang (Universitas Cenderawasih, 2023)
Research on the analysis of the structure of the soil layer using the Vertical Schlumberger Geoelectric method in the Lecturer Housing Complex of Uncen Kali Acai, VIM Village, Abepura District, Jayapura City. This study aims to determine the soil layer, determine the location and depth of the soft soil layer, determine the soft and hard soil. Data retrieval using geoelectric resistivity method with vertical Schlumberger configuration. The instrument used for subsurface surveys is the HV 500 AK resistivity meter. Field measurements obtained electric current and voltage values and then calculated the apparent resistivity values obtained from analysis using IP2win software to see the distribution profile, depth, and thickness of the soil layer.After doing research in the field, it can be seen that the subsurface structure at the research site is dominated by soft clay material with a resistivity value of 0.24 -692.00 Ωm. . In addition, there is a layer of hard rock in the form of a mixture of limestone with a resistivity value of 1181.00 - 8319.00 Ωm.. And the types of subsurface rocks found at the research site are clay, sandstone and limestone.